2006
DOI: 10.1136/ard.2005.048744
|View full text |Cite
|
Sign up to set email alerts
|

Possible role for tumour necrosis factor inhibitors in the treatment of resistant dermatomyositis and polymyositis: a retrospective study of eight patients

Abstract: Anti-TNF agents may be useful in some patients with refractory dermatomyositis or polymyositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 16 publications
0
65
1
7
Order By: Relevance
“…Several investigators have described successful use of infliximab and etanercept in refractory cases of DM; Efthimiou, et al reported that addition of etanercept or infliximab to the standard therapy of DM and polymyositis may be useful in selected cases [6][7][8] . Paradoxically, in our patient, anti-TNF-α therapy probably triggered an autoimmune phenomenon clinically manifested as DM.…”
Section: To the Editormentioning
confidence: 99%
“…Several investigators have described successful use of infliximab and etanercept in refractory cases of DM; Efthimiou, et al reported that addition of etanercept or infliximab to the standard therapy of DM and polymyositis may be useful in selected cases [6][7][8] . Paradoxically, in our patient, anti-TNF-α therapy probably triggered an autoimmune phenomenon clinically manifested as DM.…”
Section: To the Editormentioning
confidence: 99%
“…There is a need to identify therapies for patients refractory to traditional treatments. Reports have suggested improvement in inflammatory myopathies with the introduction of etanercept (5) and infliximab (5,6) in patients who were unresponsive to traditional therapies. A study of 5 patients with resistant juvenile DM reported improvement in all children with the initiation of infliximab (7).…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study of eight patients with DM/PM showed benefit in six; two failed to respond. Interestingly, both of the non-responders were older than 60 and had normal creatine kinase levels at baseline (Efthimiou et al, 2006). Studies are needed to confirm these findings and further evaluate other potential therapies being considered, like the use of costimulation blockers and B-cell depletion therapy, the latter of which may be of particular promise in DM.…”
Section: Inflammatory Myopathiesmentioning
confidence: 97%